Solution-processable and photopolymerisable TiO2 nanorods as dielectric layers for thin film transistors. Issue 43 (6th July 2020) - Cheng, Fei; Verrelli, Emanuele; Alharthi, Fahad A.; Das, Satyajit; Anthopoulos, Thomas D.; Lai, Khue T.; Kemp, Neil T.; O'Neill, Mary; Kelly, Stephen M.
Abstract : A prototype solution-processed n-type thin film transistor was fabricated. The film incorporates a dielectric layer prepared from solution-processed and photopolymerised inorganic/organic TiO2 nanorods and zinc oxide as the semiconductor, also deposited from solution. Abstract : We report the fabrication of a solution-processed n-type Thin Film Transistor (TFT) with current on/off ratios of 10 4, a turn-on voltage ( V ON ) of 1.2 V and a threshold voltage ( V T ) of 6.2 V. The TFT incorporates an insoluble and intractable dielectric layer ( k = 7–9) prepared in situ from solution-processed and then photopolymerised ligand-stabilised, inorganic/organic TiO2 nanorods. A solution processed zinc oxide (ZnO) layer acts as the semiconductor. The new surface-modified TiO2 nanorods were synthesised using a ligand replacement process with a monolayer coating of photopolymerisable 10-undecynylphosphonic acid (10UCYPA) to render them both soluble in common organic solvents and be photopolymerisable using UV-illumination after having been deposited on substrate surfaces from solution and drying.